2013
DOI: 10.4049/jimmunol.1202598
|View full text |Cite
|
Sign up to set email alerts
|

IL-16 Induces Intestinal Inflammation via PepT1 Upregulation in a Pufferfish Model: New Insights into the Molecular Mechanism of Inflammatory Bowel Disease

Abstract: Inflammatory bowel disease (IBD) has long been a worldwide health care problem with a persistently increasing incidence. Although its clinical features have been well described, its etiology and pathogenesis remain unclear. IL-16 is a chemoattractant cytokine with various effects on cellular activities and diseases. However, the involvement of IL-16 in IBD remains poorly understood. In this study, to our knowledge we report for the first time the mechanism by which IL-16 induces intestinal inflammation by upre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 75 publications
0
25
0
Order By: Relevance
“…It has been shown that IL-16 expression increase in IBD patients as compared to healthy donors [24]. Further, IL-16 exerts a strong chemoattractant activity on CD4 + cells and induces intestinal inflammation through PepT1 upregulation [43]. TNF-α is increased in the colon tissue of IBD patients [44].…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that IL-16 expression increase in IBD patients as compared to healthy donors [24]. Further, IL-16 exerts a strong chemoattractant activity on CD4 + cells and induces intestinal inflammation through PepT1 upregulation [43]. TNF-α is increased in the colon tissue of IBD patients [44].…”
Section: Discussionmentioning
confidence: 99%
“…However, colonic PepT1 expression is enhanced under conditions of chronic inflammation such as Inflammatory Bowel Disease (IBD) [4], [6], [7]. Recently, a polymorphism of the hPepT1 gene has been shown to be associated with IBD susceptibility, indicating a direct involvement of this transporter in IBD [8].…”
Section: Introductionmentioning
confidence: 99%
“…Despite the abundance of pro-and anti-inflammatory cytokines, such as IL-12, TNF-␣, IL-1␤, IL-16, and transforming growth factor ␤ (TGF-␤), that can be found in UC patients (234,237,(239)(240)(241), UC has traditionally been considered a CD4 ϩ T helper cell type 2 (Th2) disease (242,243). This view stemmed from the observation that increased levels of Th2-associated cytokines, including IL-5 and IL-13, can be measured in UC patients and experimental colitis models (239,243,244).…”
Section: Ulcerative Colitis Pathophysiologymentioning
confidence: 99%